Risk of major adverse cardiovascular events and all-cause mortality among patients with psoriatic disease treated with tumor necrosis factor-α and interleukin-12/23 inhibitors: a nationwide population-based cohort study in Korea - Hyesoo Cho; Ye-Jee Kim; Ik Jun Moon; Woo Jin Lee; Chong Hyun Won; Mi Woo Lee; Sung Eun Chang; Joon Min Jung (Taylor & Francis Group, 2024)
AbstractPurpose Few studies have investigated the impact of biologics on the risk of major adverse cardiovascular events (MACEs) among Korean patients with psoriatic diseases. We compared the risk of MACEs and all-cause mortality among patients with psoriatic disease treated with tumor necrosis factor (TNF)-α and interleukin (IL)-12/23 inhibitors in Korea.Methods Patients with psoriatic disease prescribed with TNF-α and IL-12/23 inhibitors since 2016 were selected from the Korean National Health Insurance Service (NHIS) Database. Follow-up data for MACEs and all-cause mortality between 2016 and 2020 were collected. A total of 2886 individuals were included, including 1987 IL-12/23 inhibitor users and 899 TNF-α inhibitor users.Results Compared with IL-12/23 inhibitor users, TNF-α inhibitor users had a higher prevalence of dyslipidemia and a significantly higher risk of all-cause mortality but not MACE. After controlling for age, female TNF-α inhibitor users had a significantly increased risk of all-cause mortality. Meanwhile, after controlling for sex, TNF-α inhibitor users aged 60 years or older demonstrated a significantly elevated risk of all-cause mortality. In conclusion, No statistically significant difference in MACE risk was observed between patients who used TNF-α and IL-12/23 inhibitors. Nevertheless, the use of IL-12/23 inhibitors, especially among older and female patients, resulted in a lower overall mortality.